Urban Tourism and Hospitality: Emerging challenges and trends [editorial] - Marques, Jorge (2025)
Urban tourism and hospitality are undergoing significant transformations due to technological advancements, sustainability challenges, and evolving traveler expectations. Cities are dynamic environments where tourism and hospitality intersect with urban planning, infrastructure development, and policy-making. This Special Issue seeks to address the complexities of urban tourism by exploring innovative strategies, governance models, and sustainable development approaches that shape contemporary cityscapes and tourism dynamics. Urban tourism is a critical economic driver, yet it poses challenges such as overtourism, housing shortages, environmental sustainability, and social integration. By examining the intersection of tourism and urban governance, this issue aims to shed light on how cities can develop resilient and inclusive tourism policies that balance economic benefits with local well-being. Understanding the role of smart cities, digital innovations, and mobility solutions will be crucial in fostering sustainable tourism ecosystems.